The relationship between work overload, role conflict and supervisory support on the occupational stress among nurses in Hospital in Northern Region, Malaysia - Mustaffa, Yaakob (2020)
This study primary focuses on investigating the relationship between independent variables of work overload, role conflict, supervisory support and dependent variable of occupational stress among nurses. The Job Demand Control Support (JDCS) model was utilized in explaining the relationship between the research variables in the research framework. A total of 110 nurses in one government hospital in Northern region, Malaysia participated in this study. Data were collected through questionnaire. Three hypotheses were tested using SPSS 25. The findings indicated that work overload and role conflict were significant and positively related to occupational stress among the respondents. Theoretical and practical implications of the study as well as suggestions for future research were also discussed.